Neurological and neuropsychological sequelae of Zika virus infection in children in León, Nicaragua - Jill F. Lebov; Stephen R. Hooper; Norma Pugh; Sylvia Becker-Dreps; Natalie M. Bowman; Linda M. Brown; Pia D.M. MacDonald; Premkumar Lakshmanane; Ramesh Jadi; Filemon Bucardo; Tatiana Chevez; Andrés Herrera Rodriguez; et al. (Pan American Health Organization, 2022)
Objectives. To describe the presence and persistence of neurological and neuropsychological sequelae among children with acquired Zika virus infection and assess whether those sequelae were more common in children infected with Zika virus compared to uninfected children. Methods. We conducted a prospective cohort study of children with and without Zika virus infection in León, Nicaragua, using a standard clinical assessment tool and questionnaire to collect data on symptoms at three visits, about 6 months apart, and a battery of standardized instruments to evaluate neurocognitive function, behavior, depression, and anxiety at the last two visits. Results. Sixty-two children were enrolled, with no significant differences in demographics by infection group. Children infected with Zika virus had a range of neurological symptoms, some of which persisted for 6 to 12 months; however, no consistent pattern of symptoms was observed. At baseline a small percentage of children infected with Zika virus had an abnormal finger-to-nose test (13%), cold touch response (13%), and vibration response (15%) versus 0% in the uninfected group. Neurocognitive deficits and behavioral problems were common in both groups, with no significant differences between the groups. Children infected with Zika virus had lower cognitive efficiency scores at the 6-month visit. Anxiety and depression were infrequent in both groups. Conclusions. Larger studies are needed to definitively investigate the relationship between Zika virus infection and neurological symptoms and neurocognitive problems, with adjustment for factors affecting cognition and behavior, including mood and sleep disorders, home learning environment, history of neuroinvasive infections, and detailed family history of neuropsychological problems.